The European Society of Paediatric Oncology Ependymoma-II program Core-Plus model: Development and initial implementation of a cognitive test protocol for an international brain tumour trial. (July 2019) - Thomas, S.; Reynolds, D.; Morrall, M.C.H.J.; Limond, J.; Chevignard, M.; Calaminus, G.; Poggi, G.; Bennett, E.; Frappaz, D.; Slade, D.; Gautier, J.; McQuilton, P.; et al.
Abstract: It is increasingly accepted that survival alone is an inadequate measure of the success of childhood brain tumour treatments. Consequently, there is growing emphasis on capturing quality of survival. Ependymomas are the third most frequently occurring brain tumours in childhood and present significant clinical challenges. European Society of Paediatric Oncology Ependymoma II is a comprehensive international program aiming to evaluate outcomes under different treatment regimens and improve diagnostic accuracy. Importantly, there has been agreement to lower the age at which children with posterior fossa ependymoma undergo focal irradiation from three years to either eighteen months or one year of age. Hitherto radiotherapy in Europe had been reserved for children over three years due to concerns over adverse cognitive outcomes following irradiation of the developing brain. There is therefore a duty of care to include longitudinal cognitive follow-up and this has been agreed as an essential trial outcome. Discussions between representatives of 18 participating European countries over 10 years have yielded European consensus for an internationally accepted test battery for follow-up of childhood ependymoma survivors. The 'Core-Plus' model incorporates a two-tier approach to assessment by specifying core tests to establish a minimum dataset where resources are limited, whilst maintaining scope for comprehensive assessment where feasible. The challenges leading to the development of the Core-Plus model are presented alongside learning from the initial stages of the trial. We propose that this model could provide a solution for future international trials addressing both childhood brain tumours and other conditions associated with cognitive morbidity. Highlights: Quality of survival is an important consideration in childhood brain tumour trials. We present European consensus for a cognitive follow-up model in a clinical trial. The Core-Plus battery incorporates a minimum dataset and comprehensive assessment. Challenges encountered during development and implementation are described.